Textual and Contextual Approaches to Hijab Interpretation on Instagram - Mutiara Putri Intan Safira; Husna, Rifqatul (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
The development of social media has transformed the transmission of religious knowledge and created new spaces for Qur’anic interpretation in the digital sphere. Instagram, as a visual and interactive platform, has become an important medium for Muslim preachers to articulate interpretations of Qur’anic verses on hijab to a broad audience. Although a number of studies have examined the representation of hijab on social media, most of them focus on single-account content analysis and have not comparatively explored how Qur’anic interpretive methods are constructed by digital religious actors. This study aims to analyze the construction of thematic Qur’anic interpretation (tafsir maudhu’i) regarding hijab on the Instagram accounts @ismaelalkholilie and @ismailascholy, while identifying differences in epistemological approaches in communicating religious messages in the digital space. This research employs a qualitative approach using the thematic interpretation method by focusing on verses related to hijab, such as QS. An-Nur: 31, QS. Al-Ahzab: 53 and 59, and QS. Al-A‘raf: 26. The verses are analyzed through content analysis and comparative analysis of the highlight content on both Instagram accounts. The data consist of texts, visuals, and narrative messages, which are coded to identify patterns of argumentation, interpretive references, and strategies of religious communication. The findings reveal that both accounts construct thematic interpretations of hijab by referring to classical and contemporary tafsir literature, yet through different approaches. Ismail Al-Kholilie tends to adopt a textual-normative approach grounded in classical fiqh authority, whereas Ismail Al-Ascholy develops a contextual-narrative approach integrating linguistic, literary, and social reflections. Theoretically, this study demonstrates that thematic Qur’anic interpretation on social media is undergoing methodological transformation toward a model of digital tafsir that integrates scholarly authority, visual communication strategies, and platform logic in shaping contemporary religious discourse.